A Brief Comparison of the Unconscious as Seen by Jung and Lévi‐Strauss. (March 2015) - Iurato, Giuseppe
Abstract: Retracing the primary common aspects between anthropological and psychoanalytic thought, in this article, we will further discuss the main common points between the notions of the unconscious according to Carl Gustav Jung and Claude Lévi‐Strauss, taking into account the thought of Erich Neumann. On the basis of very simple elementary logic considerations centered around the basic notion of the separation of opposites, our observations might be useful for speculations on the possible origins of rational thought and hence on the origins of consciousness.